Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species - Nunes, Rudy Camilo; Bellini, Bruno Cavalcante (Zootaxa, 2018)
Three new species of Entomobryoidea from Brazilian Caatinga-Cerrado transitional zone are described and illustrated, all from Sete Cidades National Park. Cyphoderus equidenticulati sp. nov. resembles C. javanus Börner and C. songkhlaensis Jantarit, Satasook & Deharveng in number of mucro teeth, one inner distal tooth on unguis and four ciliated chaetae between the two rows of feathered scales of dens, but differs in claw with a pair of equally developed inner basal teeth, collophore, labial and dorsal chaetotaxy. Pseudosinella triocellata sp. nov. is mostly similar to P. stewartpecki Katz, Soto-Adames & Taylor in number of eyes, presence of apical bulb on antennomere IV and one macrochaeta on mesothorax, but differs in head with S2 macrochaeta, anterior and posterior collophore chaetotaxy and empodial complex morphology. Trogolaphysa piracurucaensis sp. nov. is quite similar to the recently described T. ernersti Cipola & Bellini in overall dorsal chaetotaxy but differs in ventral head, collophore and manubrial plate chaetotaxy. Identification keys for Brazilian species of Cyphoderus, Pseudosinella and Trogolaphysa are also provided.